2019
DOI: 10.1093/ndt/gfz208
|View full text |Cite
|
Sign up to set email alerts
|

Survival of patients treated with extended-hours haemodialysis in Europe: an analysis of the ERA-EDTA Registry

Abstract: Background Previous US studies have indicated that haemodialysis with ≥6-h sessions [extended-hours haemodialysis (EHD)] may improve patient survival. However, patient characteristics and treatment practices vary between the USA and Europe. We therefore investigated the effect of EHD three times weekly on survival compared with conventional haemodialysis (CHD) among European patients. Methods We included patients who were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…[16][17][18] Work by Tentori et al showed that over time most European countries included in the Dialysis Outcomes and Practice Patterns Study had a longer HD session time, which was associated with a lower mortality risk. 19,20 In addition, a decrease in interdialytic weight gain, as shown from phase 2 to 5 in the Dialysis Outcomes and Practice Patterns Study, may have led to a reduction in intradialytic hypotensive episodes, thereby contributing to the enhanced survival. 21 The lack of improvement of the excess mortality risk in PD patients may be due to the lower excess mortality rates, leaving less room for improvement over time.…”
Section: Trends In Dialysis Patientsmentioning
confidence: 99%
“…[16][17][18] Work by Tentori et al showed that over time most European countries included in the Dialysis Outcomes and Practice Patterns Study had a longer HD session time, which was associated with a lower mortality risk. 19,20 In addition, a decrease in interdialytic weight gain, as shown from phase 2 to 5 in the Dialysis Outcomes and Practice Patterns Study, may have led to a reduction in intradialytic hypotensive episodes, thereby contributing to the enhanced survival. 21 The lack of improvement of the excess mortality risk in PD patients may be due to the lower excess mortality rates, leaving less room for improvement over time.…”
Section: Trends In Dialysis Patientsmentioning
confidence: 99%
“…3,4,21,22 This suggests that our cohort was representative of patients typically offered more intensive dialysis schedules, who are known to have better prognostic characteristics than those performing standard hours. 2,6,11 Cohort studies utilize a variety of matching methodologies to account for the difference in the characteristics of people practising more intensive dialysis schedules when assessing the impact of these schedules and obtain wide variation in estimates of the survival benefit. 2,6,7,23,24 The present study thus suggests that residual confounding by patient selection in observational studies of extended or more intensive dialysis may be more important that previously acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have demonstrated a survival advantage with additional dialysis. 1,2 For instance, the 5-year survival of 70% to 80% seen in cohorts of extended hours haemodialysis (24 h/wk, typically over 3 sessions) 3,4 far exceeds the 50% 5-year survival seen in general haemodialysis cohorts. 5 Yet the quality of the evidence in favour of longer dialysis hours remains low, primarily owing to the dependence on observational data which cannot eliminate residual confounding due to the characteristics of patients or centres choosing to perform intensive haemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…Longer weekly duration was recorded in HHD than in ICHD, with a wider range of treatment times. A European study assessing treatment duration from the ERA‐EDTA Registry also found that patients on extended‐hours haemodialysis (defined as thrice weekly ≥6 hours sessions) were more often treated at home than patients on conventional haemodialysis (thrice weekly 3.5 to 4‐hours sessions) (6% vs 0%) 12 . In ANZ, no financial incentives or penalties and no official policies or guidelines are in place regarding the required treatment duration.…”
Section: Discussionmentioning
confidence: 99%
“…In 1981, the National Cooperative Dialysis Study, aiming to develop a definition of adequate long‐term dialysis treatment by evaluating different concentrations of blood urea nitrogen (BUN) and treatment times, found that shorter treatment duration appeared to contribute to morbidity 1 . Since then, many observational studies have associated longer dialysis duration with lower mortality 2‐12 . Among these, a registry analysis from Australia and New Zealand in 2006 concluded that the optimal combination of haemodialysis treatment for better survival appeared to be Kt/V ≥ 1.3 and session length of ≥4.5 hours 6 .…”
mentioning
confidence: 99%